2013
DOI: 10.1111/cge.12276
|View full text |Cite
|
Sign up to set email alerts
|

Polydactyly: phenotypes, genetics and classification

Abstract: Polydactyly is one of the most common hereditary limb malformations featuring additional digits in hands and/or feet. It constituted the highest proportion among the congenital limb defects in various epidemiological surveys. Polydactyly, primarily presenting as an additional pre-axial or post-axial digit of autopod, is a highly heterogeneous condition and depicts broad inter- and intra-familial clinical variability. There is a plethora of polydactyly classification methods reported in the medical literature w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
135
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(146 citation statements)
references
References 35 publications
6
135
0
5
Order By: Relevance
“…Actually, the cases with point mutations and the cases with contiguous deletions manifest highly overlapping phenotypes, and it is not easy to distinguish these 2 conditions. Specifically, GLI3 is particularly important for finger development [Malik, 2014], and a deficiency of GLI2A, which is an activator form of GLI2, especially affects pituitary and midface development [Gregory et al, 2015]. The fact that GLI2 and GLI3 gene mutations exhibit different phenotypes in humans indicates that each GLI gene became functionally differentiated through evolution, and GLI2 and GLI3 proteins play different roles during embryonic development.…”
mentioning
confidence: 99%
“…Actually, the cases with point mutations and the cases with contiguous deletions manifest highly overlapping phenotypes, and it is not easy to distinguish these 2 conditions. Specifically, GLI3 is particularly important for finger development [Malik, 2014], and a deficiency of GLI2A, which is an activator form of GLI2, especially affects pituitary and midface development [Gregory et al, 2015]. The fact that GLI2 and GLI3 gene mutations exhibit different phenotypes in humans indicates that each GLI gene became functionally differentiated through evolution, and GLI2 and GLI3 proteins play different roles during embryonic development.…”
mentioning
confidence: 99%
“…Recently, two independent studies using different mouse models have shown that CYLD is required for ciliogenesis. We have found that Cyld-knockout mice exhibit polydactyly, a cilium-associated symptom (Malik, 2014), and defective ciliogenesis in multiple organs, including the skin, kidney, trachea and testis (Yang et al, 2014b). Transmission electron microscopy showed that CYLD is required for the anchorage of the basal body and proper organization of the basal body and axoneme (Fig.…”
Section: Cyld Is Crucially Involved In Ciliogenesismentioning
confidence: 94%
“…It is one of the most common congenital deformities [2]. The worldwide incidence of PPD is 1 in 3000 births [3].…”
Section: Main Textmentioning
confidence: 99%
“…The prevalence rate of polydactyly in Chinese ranks third in birth defects after congenital heart diseases and central nervous system diseases [4]. Polydactyly has genetic and clinical heterogeneity [2]. The mainstream treatment is resection for excess digits.…”
Section: Main Textmentioning
confidence: 99%